INCIDENCE OF PREGNANCY RELATED ACUTE KIDNEY INJURY DUE TO SEPSIS AT SIR GANGA RAM HOSPITAL, A PROSPECTIVE STUDY USING THE SEPSIS IN OBSTETRICS SCORE (The Research of Medical Science Review, 2025)
Background: Pregnancy-related acute kidney injury (PR-AKI) is a serious complication that increases maternal and fetal morbidity and mortality, particularly when associated with sepsis. Early identification using clinical scoring systems such as the Sepsis in Obstetrics Score (SOS) can improve outcomes. Objective: To determine the incidence, clinical characteristics, and outcomes of sepsis-induced pregnancy-related acute kidney injury using the Sepsis in Obstetrics Score. Methods: This descriptive case series was conducted at Sir Ganga Ram Hospital, Lahore from January 2025 to March 2025, and included 246 pregnant or postpartum patients admitted with sepsis. Patients were followed for the development of AKI, defined as serum creatinine ≥1 mg/dL or a 0.5 mg/dL rise within 48 hours. Clinical and laboratory data were collected and analyzed using SPSS. Results: Among the 246 participants, 108 (44%) developed AKI. Patients with AKI had significantly higher SOS scores (14.9 ± 3.2 vs. 10.4 ± 2.9, p < 0.001), lower systolic blood pressure, and higher lactic acid and WBC counts. A strong correlation was observed between SOS score and AKI stage (rho = 0.63, p < 0.001). Dialysis was required in 17.6% of AKI cases, and 5.6% resulted in maternal death. AKI incidence was significantly higher among patients without antenatal care (87.2%) and those who underwent cesarean delivery (57.9%). Conclusion: Sepsis is a leading cause of PR-AKI in low-resource settings. The Sepsis in Obstetrics Score is a valuable tool for early identification and risk stratification. Prompt recognition and multidisciplinary management may help reduce adverse maternal and fetal outcomes.